2000
DOI: 10.1161/01.hyp.35.3.769
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of Combination of Perindopril, Candesartan, and Amlodipine in Hypertensive Rats

Abstract: Abstract-The combination therapy with ACE inhibitors, angiotensin II type 1 (AT 1 ) receptor antagonists, or calcium channel antagonists may exert more beneficial effects on cardiovascular diseases than monotherapy. Perindopril, candesartan cilexetil, or amlodipine alone or the combination of low doses of each agent was administered orally to stroke-prone spontaneously hypertensive rats (SHRSP) for 4 weeks to compare the hypotensive or cardiovascular effects. Although perindopril (2 mg/kg), candesartan cilexet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 41 publications
3
23
0
Order By: Relevance
“…Benidipine (10,11) and candesartan cilexetil (12,13) were obtained from Kyowa Hakko Kogyo Co., Ltd. (Tokyo, Japan). Cilazapril was the gift of Eizai Co., Ltd (Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Benidipine (10,11) and candesartan cilexetil (12,13) were obtained from Kyowa Hakko Kogyo Co., Ltd. (Tokyo, Japan). Cilazapril was the gift of Eizai Co., Ltd (Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…At 6 weeks of age, the diet was switched to an 8% NaCl diet, and the rats were divided into 8 groups that were respectively treated with 1) vehicle (0.5% carboxymethylcellulose solution), 2) benidipine (1 mg/kg/day), 3) benidipine (3 mg/kg/day), 4) benidipine (6 mg/kg/day), 5) candesartan cilexetil (3 mg/kg/day), 6) cilazapril (10 mg/kg/day), 7) benidipine (3 mg/kg/day) and candesartan cilexetil (3 mg/kg/day), and 8) benidipine (3 mg/kg/day) and cilazapril (10 mg/kg/day). We have previously reported that the present doses of cilazapril (10 mg/kg/day) and candesartan (3 mg/kg/day) were pharmacologically sufficient to exert a significant hypotensive effect, a significant inhibition of cardiac hypertrophy, or a significant improvement of renal impairment in hypertensive or diabetic rats (1,(12)(13)(14)(15)(16)(17). All drugs were orally administered to DS rats by gastric gavage once a day until 16 weeks of age (i.e., for 10 weeks).…”
Section: Experimental Animals and Protocolmentioning
confidence: 95%
“…SHRSP is the most popular model of genetic hypertension and is the very useful model of hypertensive cardiac hypertrophy and remodeling. 11,14,15,20 We have previously shown that SHRSP exhibits cardiac hypertrophy and upregulation of cardiac hypertrophyand remodeling-associated gene expression, compared with normotensive rats. 11,15 Moreover, we have reported that cardiac AP1 activity related to c-Jun is significantly increased in SHRSP compared with normotensive rats.…”
Section: Cardiacmentioning
confidence: 99%
“…In our previous study, we reported that combination treatment with an ACE inhibitor and an ARB had similar beneficial effects on stroke-prone spontaneously hypertensive rats (23) and on a rat model of balloon-injured intimal hyperplasia (24). However, it remains to be determined whether or not the combination of an ARB or an ACE inhibitor with a calcium channel blocker has additive beneficial effects in this model.…”
Section: Discussionmentioning
confidence: 96%